Concepções dos professores da educação básica sobre as feiras de ciência - Souza, Thaianne Lopes de (2016)
Currently the Science fairs in Brazil have gained great incentive, examples are the regulations that the government has been implementing in education and the financing of public calls for events throughout the national territory. However, even with this incentive, some researchers point out that the scientific fairs and shows are still interpreted as an extemporaneous work by teachers. In order to know the views of basic education teachers about the fairs of Science, proposed to carry out this research. Given this situation, based mediation theory and sociocultural interaction Vygotsky (2001), the theory of instrumentalism Dewey (2002) and the proposed education through research Galiazzi e Moraes (2002), we sought to understand the importance of fair and their benefits as well as the presence in the talks of respondents. In order to analyze the answers of respondents, used to discourse analysis proposed by Eni Orlandi (2009), in which it is observed and is an interpretation of the speech of teachers, considering their interpretation and how to shape their thinking on the research object. In analyzing the results of the survey, it was noted that the teachers interviewed know the importance and objectives of science fairs, however experience difficulties that often does not allow these events to be carried out. In seeking to assist them to minimize these difficulties, it was realized the need for a product to make available guidance on how to develop research projects and assemblies of science fairs, that would provide an education for the research. Thus, resulting from research, was set up a blog and a booklet with texts, articles and report templates.